Petrol Subsidy Removal as an Instrument for Greenhouse Gases Reduction in Nigeria - Abdulkareem, Jamil Hassan; Otaru, Fatima Zahra Abubakar-; Richard, Ronas (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
The removal of petrol subsidy in Nigeria has significantly reduced fuel consumption among the nation’s citizens from January 2023 to August 2023 and has caused untold hardship on the citizens of Nigeria. However, it is important to understand from environmental perspective that this development has contributed to a significant decline in green gases emission thereby reducing the negative impact on climate change. The aim of this research is to study the effect of petrol subsidy removal as an instrument for greenhouse gases reduction in Nigeria. Furthermore, a cross-section of Nigerians was interviewed on subsidy removal on petrol, however, 65 percent of low-income, 25 percent of middle-income earners while 10 Percent of higher-income earners have shown their dismay on subsidy removal in the country. This study adopted a qualitative and quantitative research approach so as to adequately describe the study’s aims and objectives. The data for this study were collected through primary and scientific database sources, web search engines, direct observation and relevant documents from the Nigeria Midstream and Downstream Petroleum Regulatory Authority (NMDPRA), International Monetary Fund, Climate Transparency Report and Nigerian News Papers.